Does doing good, do good : an investigation into SRI fund performance in South Africa - Fredericks, Llewellyn (Department of Finance and Tax, 2014)
In this paper the literature is reviewed to determine what exactly SRI is, and whether there has been evidence of the financial benefits of SRI compared to conventional portfolios internationally. It has been found that among the different opinions of SRI, four goals of SRI are central to understanding the concept. These goals are essentially to democratize the economy (by encouraging the employment and empowerment of the previously disadvantaged), to humanize the work environment (ensuring the safety and training of staff), rethinking profit distribution (dividends versus charitable giving and environmental campaigns) and convincing the business world that a corporate conscience can pay. With regards to gaining evidence of the financial benefits of SRI compared to conventional portfolios, no greater clarity was obtained, since there was diverging results of the studies undertaken. These results ranged from views that there is no trade-off between the two different stock performances, while others show that SRI stocks outperform non-SRI stocks and also that 'sin' stocks outperform SRI stocks.